The portrayal of disabled character in Paola Peretti’s The Distance Between Me and the Cherry Tree (2018) - Fhadillah, Aulia Virdha (Passage: Journal of English Language and Literature, 2024)
Disability is a natural and inherent aspect of human diversity. This issue also becomes a relevant topic in literary works, for example novels. In novels, the existence of disability can influence and shape the readers’ perspective about it. Using Reams’ (2015) theory of characterization, this qualitative study aims to examine how the main character of The Distance Between Me and the Cherry Tree (2018) is positively portrayed and conveyed through narrations and dialogues. This study found that the main character is presented through three categories of characterization during two phases of her disabled experience, the denial phase and the acceptance phase. After experiencing physical changes and emotional upheaval as the effect of losing visual ability, the main character is portrayed as having an improved hearing ability, independent, confident, and brave in facing difficulties as a disabled person. The case of this study is expected to give insights into the challenges and daily experiences of individuals with disabilities and facilitate the growth of people’s awareness of disability.